The Economic Determinants of the CO2 Emission in Saudi Arabia: The role and impact - ALmalki, Amal Hassan; Samargandi, Nahla Sadrudden; Bokhari, Abla Abdulhameed (Journal of Economic, Administrative and Legal Sciences, 2019)
This study examined the impact of a number of economic determinants such as economic growth, electricity consumption, foreign direct investment, financial development, trade openness and their contribution to increase or decrease of carbon dioxide (CO2) emissions in Saudi Arabia. To explore the long-run relationships between the variables, the autoregressive distributed lag (ARDL) methodology, is employed to analyze time series data for the period 1980-2017. Results indicates that there has is a long-term positive relationship between electricity consumption, economic growth, trade openness, and carbon dioxide emissions. A long-term negative relationship is existed between both foreign direct investment and the financial development, and carbon dioxide emissions. Therefore, we see how important it is to reduce dependence on fossil fuels and switch to renewable energy in electricity production. This indicates the importance of Vision 2030 to reduce dependence on oil as a major source of income and to support economic growth by developing the non-oil sector. And the importance of raising the efficiency of funding and providing the necessary liquidity to support the industrial sectors with the imposition of strict environmental laws.
Keywords: carbon dioxide emissions; sustainable development; global warming; renewable energy; economic growth